Diagnóstico físico conservacionista da Bacia Hidrográfica do Ribeirão Jerusalém, Alegre-ES - Venturim, George Hilton (2011)
The Atlantic Forest is among the most biodiverse of the tropical rainforests and also the most vulnerable of the planet Earth. Over 93% of the forest cover has already been destroyed and the tiny remaining 7% are under serious threat. In the state of the Holy Spirit remains 11% of the Atlantic Forest in various stages of conservation and regeneration. The municipality of Alegre, in the south of the State, is located in the Jerusalém River Hydrographic Basin - BHRJ, the main source of water supply for the county seat, but the inappropriate use of land, with occupation of Permanent Preservation Areas (PPA) for productive purposes has significantly affected the environmental quality of the basin. The objective of this study was to conduct a physical diagnosis for conservation in the BHRJ, through the applicability of Geographic Information Systems (GIS) featuring some morphometric aspects, land use and estimates of soil loss, especially in areas Permanent Preservation (PPA). The total area reserved for the PPA BHRJ is 29.88 km², representing 43.99% of the basin area, however 84.2% of this area presents conflicting use. So it is necessary to recompose 25.44 km². Among the categories of PPA, the largest reduction in area of native vegetation occurred in PPA4 (stream margins). The class of land use is predominantly pasture occupying 65.57% of the area of the BHRJ, with 42.18% occurring in PPA. Coffee plantation is the second most popular activity conflicting with 10.7% of misuse. There are 93% of urban and rural constructions and facilities precisely located in riparian areas and flood zones, that is, in imminent danger of flooding when rainfall rates increase. The estimation of soil loss showed that the total average loss in the BHRJ was 394,139.76 tons/year and in the PPA 139,479.84 tons/year. Between the PPA and PPA1 (hilltop) there is the highest total average loss. To estimate in the classes of land use, pasture and coffee plantations had the greatest contribution in terms of origins for sediment to the water resources in the Jerusalem River Basin. We conclude that it is necessary a new model of municipal environmental management regarding river basins, especially the BHRJ. The integration between scientific research and application of environmental policies and instruments of environmental policies is a premise for the reversal of environmental degradation in this basin. It is fundamental for the integration of farmers in the process of forest recovery in the Atlantic Biome the implementation of actions in environmental education and also the convergence of public policies adaptable to the local agricultural and environmental conditions, which are economically viable and non-predatory to the local ecosystems